Advanced bandages for diabetic wound healing - Matoori, Simon; Veves, Aristidis; Mooney, David J (Science translational medicine, 2021)
Current treatment options for foot ulcers, a serious and prevalent complication of diabetes, remain nonspecific. In this Perspective, we present recent advances in understanding the pathophysiology of diabetic wound healing and the emergence of previously unidentified targets. We discuss wound dressings tailored to the diabetic wound environment currently under development.